Penerapan Instrumen Industri 4.0: Analisis SWOT Sebagai Strategi Transformasi Industri 4.0 di CV.Muda Teknindo - Agustin, Desy; Nurhadi, Fadhil Fadhlurrohman; Nurhadi, Hikari Qurrata’ain; Achmad, Faiz Aditya (Politeknik STMI Jakarta, 2025)
The application of Industry 4.0 instruments is important to increase company competitiveness in the digital era. CV. Muda Teknindo, which has produced products such as the Programmable Logic Controller (PLC), seeks to carry out a broader industrial transformation. In order to assess the company's readiness to implement industry 4.0, this community partnership program (PKM) involves lecturers and staff in conducting a survey on the fulfillment of 4.0 readiness indicators at CV. Muda Teknindo. The recapitulation results of the survey show that the average value of respondent 1 is 1.172 and respondent 2 is 1.148. This assessment shows that CV. Muda Teknindo is at level 1 in terms of industrial transformation 4.0, which indicates an urgent need for further development. To overcome these challenges, the next step in this PKM is to carry out a SWOT analysis so that you can get the right strategy for implementing Indi 4.0 in industry. The SWOT process involves brainstorming which is expected to produce concrete strategies that can be implemented to increase the company's readiness and capacity towards implementing technology 4.0 more effectively. The resulting recommendations will include employee skills development, business model recommendations, and strengthening the culture of innovation within the company. Therefore, this PKM does not only aim to improve CV Muda Teknindo in handling industrial transformation, but also contributing to the development of a local industrial sector that is more adaptive and highly competitive.